Persepsi Masyarakat Indonesia Terhadap Peran Apoteker Komunitas Dalam Pengkajian Resep Dan Pemberian Obat Berdasarkan Tingkat Pendidikan Masyarakat - Ndruru, Joyce Nadia Clarita; Soegiantoro, Didiek Hardiyanto; Rawar, Ellsya Angeline (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
Community pharmacists play a crucial role in pharmaceutical practice in Indonesia, including prescription compounding and medication dispensing. The impact of community education on perceptions of the role of community pharmacists in prescription assessment and medication dispensing has never been investigated. The aim of this study was to determine the impact of respondents' education on perceptions of the role of community pharmacists regarding general awareness (GA), effectiveness (EFF), collaborative care (COLL), barriers (BARR), trustworthiness (TRUST), and prescription review and administration (PRPO) based on respondents' education level. Data were collected from a 21-item questionnaire and analyzed quantitatively and descriptively using a cross-sectional design. The sample size was determined using the Cochran formula, resulting in 100 respondents, with an additional 50 respondents added to the validity test. A significance value of 0.000 and a Cronbach's Alpha value of 0.65 indicated that the questionnaire was valid and reliable. The results of statistical analysis using the chi-square test indicate an influence between education level on public perception regarding general awareness (GA), collaborative (COLL), barriers (BARR), trustworthiness (TRUST), while there is no influence between education level on public perception regarding effectiveness (EFF) and prescription review and administration (PRPO). The Spearman rank correlation of this study shows that the pair of variables that have a statistically significant relationship between EFF and PRPO has the highest correlation value (r=0.412).